Developing interactive SAC-based media to enhance elementary IPAS learning - Rosida Minta Ito Pasaribu; Samsidar Tanjung; Yusnadi Yusnadi (Himpunan Pengembang Kurikulum Indonesia, 2025)
This research was conducted based on a needs analysis regarding interactive digital learning media to improve student learning outcomes in the IPAS subject. Teachers still predominantly use conventional methods and limited media, resulting in low student motivation and difficulty in understanding the material in depth. The low learning outcomes of students in the IPAS subject at SD Negeri 0401 Pasar Ujung Batu are caused by the minimal use of interactive learning media. The purpose of this study is to develop, test the feasibility, and examine the effectiveness of interactive learning media based on Smart Apps Creator (SAC) in improving the IPAS learning outcomes of fourth-grade elementary school students. The rationale for conducting this research lies in the demand for digital learning media that can enhance students’ motivation, engagement, and comprehension of the learning material, particularly within the framework of the Merdeka Curriculum, which emphasizes more contextual and enjoyable learning. The method employed was Research and Development (RnD) using the Four-D model (Define, Design, Develop, Disseminate). The findings revealed that the developed media was deemed feasible by experts, highly practical by teachers and students, and effective in improving learning outcomes with a medium level of improvement. These results indicate that SAC-based interactive media can serve as a relevant and innovative learning solution in the digital era. Abstrak Penelitian ini dilakukan berdasarkan hasil analisis kebutuhan akan media pembelajaran digital yang interaktif untuk meningkatkan hasil belajar peserta didik dalam mata pelajaran IPAS. Guru masih dominan menggunakan metode konvensional dan media yang terbatas, sehingga peserta didik kurang termotivasi dan sulit memahami materi secara mendalam. Rendahnya hasil belajar peserta didik pada mata pelajaran IPAS di SD Negeri 0401 Pasar Ujung Batu yang disebabkan oleh minimnya penggunaan media pembelajaran interaktif. Tujuan dari penelitian ini adalah untuk mengembangkan dan menguji kelayakan serta efektivitas media pembelajaran interaktif berbasis Smart Apps Creator (SAC) dalam meningkatkan hasil belajar IPAS peserta didik kelas IV SD. Alasan dilakukannya penelitian ini adalah karena kebutuhan akan media pembelajaran digital yang mampu meningkatkan motivasi, keterlibatan, dan pemahaman peserta didik terhadap materi pembelajaran, khususnya pada Kurikulum Merdeka yang menuntut pembelajaran lebih kontekstual dan menyenangkan. Metode yang digunakan adalah penelitian pengembangan (Research and Development) dengan model Four-D (Define, Design, Develop, Disseminate). Hasil penelitian menunjukkan bahwa media yang dikembangkan dinyatakan layak oleh ahli, sangat praktis oleh guru dan peserta didik, serta efektif meningkatkan hasil belajar dengan kategori peningkatan sedang. Temuan ini menunjukkan bahwa media interaktif berbasis SAC dapat menjadi solusi pembelajaran yang relevan dan inovatif di era digital. Kata Kunci: media belajar digital; media interaktif; SAC; Smart Apps Creator